A escola pública e o Ministério Público: mecanismos de promoção de participação da sociedade civil nas soluções dos problemas ambientais (a partir da utilização do APP “NatureSpe – Uma Esperança Certa”) - Santos, Flávio Fonseca (2021)
This dissertation aims to foster the formation of a partnership between the (public) school and the public prosecutor, as a way to expand Environmental Education, from the perspective of Communicative Action, as a possibility for the emancipation of the social subject. The locus of the research would be initially at Colégio Estadual Gumercindo Bessa, which is located in the Porto D’areia neighborhood, in the city of Estância-SE; but, due to the pandemic that gave rise to the need for social isolation, the research had to be readjusted, becoming just a bibliographic study, since it was no longer possible for the initial research subjects to participate. The study is aimed at awakening the need to form partnerships between the school and institutions, with the aim of fostering a critical sense of students and drawing attention to the environmental issue, as well as for students to become citizens participating in the solutions to environmental problems. The methodological procedure that supported the research was based on Habermas' Theory of Communicative Action, and the study was supported by the philosophy and teachings on dialogicity by the illustrious Paulo Freire. It was found that with speech acts, from the linguistic interactions, it was possible to perceive, in view of the verbal meaning, the speaker's true intentions, and, mainly, to understand the type of action performed. The methodological path pursued also allowed us to perceive how intersubjective relationships take place in the world of people's lives. After all the discussions and studies, it was possible to build an educational product, namely: the creation of an application, whose name is "NatureSpe - A sure hope", capable of being applied at school and replicable in other realities, so that students and/or users can deepen their knowledge about environmental crimes and, at the end, file complaints when they become aware of the practice of any environmental damage.